EFEKTIVITAS PERAN MUDIN (KASI KESRA) DI MASYARAKAT DALAM PENCATATAN PERKAWINAN - Lailatut Thoyyibah; Abdullah Afif (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effectiveness of Mudin (Kasi Kesra) as Marriage Registration Assistants (P3N) in the marriage registration process at KUA Perak District, Jombang Regency. Despite the formal abolition of P3N roles under the Director General’s Instruction No. DJ.II/1/2015, Mudin remains actively involved in assisting communities with marriage administration. A qualitative empirical-juridical approach was employed, with in-depth interviews conducted with three Mudin and the Head of KUA Perak. The findings reveal that Mudin acts as a facilitator between the community and KUA, with duties including: (1) assisting marriage document preparation, (2) verifying administrative requirements, (3) providing procedural information, and (4) recording marriage events. Their role enhances service efficiency, minimizes administrative errors, and improves community access to KUA. However, challenges include the lack of legal recognition, limited training, and low public awareness of marriage registration. The study recommends governmental recognition and capacity-building for Mudin, alongside public education on marriage registration. These findings highlight the significance of traditional institutions in supporting religion-based civil administration policies.